Comparison of Clinical Features of Intervertebral Disc Extrusions in English Cocker Spaniels, French Bulldogs and Dachshunds - Jad Abouzeid; Nick Grapes; Sam Khan; Steven De Decker; Paul Freeman (Animals)
Intervertebral disc extrusion (IVDE) is a common neurological condition in veterinary medicine, with chondrodystrophic breeds being particularly susceptible. Studies have compared breed-related risks and clinical characteristics, but here, we investigate the disease in three common chondrodystrophic breeds, the English cocker spaniel, French bulldog and dachshund, and aim to describe and compare the clinical features and anatomical distribution between them. We performed a multicentre retrospective observational study that included 465 dachshunds, 327 French bulldogs and 145 English cocker spaniels with an imaging confirmed diagnosis of IVDE. The mean age at presentation differed in all three breeds, with the French bulldog presenting youngest and English cocker spaniels presenting oldest. IVDE was most common in the thoracolumbar region in all three breeds, although French bulldogs showed the highest proportion of cervical IVDE, dachshunds the highest proportion of thoracolumbar IVDE, and English cocker spaniels the highest proportion of lumbosacral IVDE. The results of this study suggest a differing clinical presentation for IVDE between these three breeds with regard to both the age of onset and the anatomical region most likely to be affected.